Infiltrasi Dalam Penafsiran Al-Qur`An: Studi Atas Penafsiran As-Syaukani Pada Surat Yusuf - Farhati, Wahdah (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2020)
Abstract: Qasas Al-Qur ʻan is one of the main contents of the Qur'an that gives ibrah or lessons for humans. The existence of Muhkam verses and mutasyabih in the Qur'an makes mufassirs try to understand and look for the completeness of a success story not a few mufassirs who use infiltration in its interpretation in order to obtain complete information. This research is present as an effort to uncover infiltration in the commentary book Fath al-Qadir by as-Syaukani and study the implications of infiltration involvement in his interpretation aimed at the story of the prophet Yusuf. Suggestions used are hadith criticism and interpretation. The results of this study published about Fath al-Qadir's interpretation contain infiltration because the discovery of using the hadith dha'if, maudhu 'and israiliyyat, has implications for the interpretation of Ash-Syaukani which uses information available in the Koran and hadith and the ability to visit is valid with the invalid. Keywords: Infiltration; Ash-Syaukani; Tafsir Fath al-Qadir; Qasas Al-Qur`an; da'eef; maudhu; sahih. Abstrak Abstrak: Qasas Al-Qur`an merupakan salah satu pokok isi kandungan Al-Qur`an yang bertujuan memberikan ibrah atau pelajaran bagi manusia. Keberadaan ayat Muhkam dan mutasyabih dalam Al-Qur`an membuat para mufassir mencoba memahami dan mencari-cari kelengkapan dari suatu kisah sehingga tidak sedikit para mufassir yang terjebak pada infiltrasi dalam penafsirannya guna mendapatkan informasi yang lengkap. Penelitian ini hadir sebagai upaya mengungkap infiltrasi dalam kitab tafsir Fath al-Qadir karya as-Syaukani dan mengetahui implikasi dari kehadiran infiltrasi dalam tafsirnya terutama pada kisah nabi Yusuf. Pendekatan yang digunakan adalah kritik hadis dan tafsir. Hasil dari penelitian ini membukitan bahwa tafsir Fath al-Qadir mengandung infiltrasi karena ditemukannya penggunaan hadis dha’if, maudhu’ dan israiliyyat, sehingga berimplikasi pada penafsiran Asy-Syaukani yang mengandung informasi yang tidak ada dalam Al-Qur`an dan hadis serta bercampunya riwayat sahih dengan yang tidak sahih. Kata kunci: Infiltrasi; Asy-Syaukani; Tafsir Fath al-Qadir; Qasas Al-Qur`an; dhaif; maudhu; sahih.